Modern medical ethics and viewpoints in the field of stem cell - Samira Gilanchi; Nayeb Ali Ahmadi; Asghar Ashrafi Hafez (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. There are advanced improvements in medical knowledge and technology. Identification and isolating of the stem cells is one of the new findings in medical sciences. The stem cells have high potential in duplication and differentiation into specialized cells; they have high capability in tissue repairing. For that reason, they have been mattered by researchers. As the science and technology improves, ethical viewpoints surround it more. Discussion and contention on ethical problems of stem cells continues from argument about type of stem cells to their basic and clinical utilization. Thus, research and exploring about this science must be lined up ethical aspects. Since Islamic Republic of Iran is among the first countries using technology of the stem cells, and Iranian researches have focused on studying these cells, therefore, we have studied on main medical ethics of the stem cells  Keywords: Medical ethics, Stem cells, Inducible stem cells For downloading the full-text of this article please click here.